2013
DOI: 10.2166/wst.2013.356
|View full text |Cite
|
Sign up to set email alerts
|

Removal of titanium dioxide nanoparticles by coagulation: effects of coagulants, typical ions, alkalinity and natural organic matters

Abstract: To investigate the possibility of removing titanium dioxide nanoparticles (TiO2 NPs) from water by coagulation, as well as to find the optimal coagulant and experimental conditions for TiO2 NP removal, four types of coagulant were adopted: polyferric sulfate (PFS), ferric chloride (FeCl3), polyaluminum chloride (PACl), and alum (Al2(SO4)3). It was found that the removal of TiO2 NPs by coagulation was affected by ionic strength, alkalinity, as well as types and dosages of coagulants. PFS and FeCl3 achieved much… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 2 publications
4
26
0
Order By: Relevance
“…The presence of humic acid (HA) greatly decreased the removal rate of TiO2 and nC60 ) because of the steric hindrance effects of HA molecules on nanoparticles and the additional negative charge imparted to the nanoparticles. A similar conclusion was drawn in other studies on coagulation of TiO2 (H. Wang et al, 2013) and Ag by 4 different coagulants (alum, ferric chloride, polyaluminum chloride, polyferric sulfate) independently on coagulant type. Alkalinity positively affected nC60 removal during alum coagulation .…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…The presence of humic acid (HA) greatly decreased the removal rate of TiO2 and nC60 ) because of the steric hindrance effects of HA molecules on nanoparticles and the additional negative charge imparted to the nanoparticles. A similar conclusion was drawn in other studies on coagulation of TiO2 (H. Wang et al, 2013) and Ag by 4 different coagulants (alum, ferric chloride, polyaluminum chloride, polyferric sulfate) independently on coagulant type. Alkalinity positively affected nC60 removal during alum coagulation .…”
Section: Introductionsupporting
confidence: 88%
“…Removal efficiencies of eNPs applying coagulation-flocculation-sedimentation (CFS) processes were investigated in several studies. The list of eNPs studied includes TiO2 (H. Wang et al, 2013;, Fe2O3, ZnO, NiO (Yang Zhang et al, 2008), silica (Chang et al, 2007;Yang Zhang et al, 2008), multi-walled carbon nanotubes (CNTs) , quantum dots (QDs) (Y. ,…”
Section: Coagulation Flocculation Sedimentationmentioning
confidence: 99%
See 1 more Smart Citation
“…After release into an aquatic environment, water chemistry has significant effect on the aggregation and stability of NPs [14,33,34]. Understanding the aggregation of NPs is essential for predicting their fate and transport in aqueous systems [35].…”
Section: Nanoparticlesmentioning
confidence: 99%
“…We chose PFS and FeCl 3 as coagulants because they are widely used in drinking water treatment, and our previous study has indicated that PFS and FeCl 3 have better performance than other coagulants such as polyaluminum chloride (PACl) and alum (Al 2 (SO 4 ) 3 ) for the removal of TiO 2 NPs [16]. The finding of this study is expected to provide fundamental understanding of the reaction between TiO 2 NPs and coagulants, as well as to provide a practical solution for the separation of TiO 2 NPs from water.…”
Section: Introductionmentioning
confidence: 99%